1972
DOI: 10.1139/b72-127
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Krebs cycle and pentose phosphate pathway activities in the control of dormancy of Avena fatua

Abstract: SIMMONDS, J. A., and G. M. SIMPSON. 1972. Regulation of the Krebs cycle and pentose phosphate pathway activities in the control of dormancy of Avet~a fntrra. Can. J . Bot. 50: 1041-1048. Malonic acid (10-2 M ) promoted germination of excised dormant embryos of Averia fntrra L. but inhibited germination of non-dormant embryos. Malonate inhibited oxygen consun~ption and carbon dioxide evolution of dormant embryos which resulted in an increased respiratory quotient and a decrease in the glucose C6/C1 ratio. Germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
2

Year Published

1974
1974
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 15 publications
1
11
2
Order By: Relevance
“…The activity of catalase was decreased by cool winter temperatures and dormancy-breaking chemicals such as cyanamide and thiourea. It is possible, as previously suggested for seeds (17,19,20), and found by us in grapevine buds (G. Nir, S Lavee, unpublished data), that the decrease in catalase activity causes an increase in the level of H202 in bud tissue. The increased level of H202 might cause the activation of the pentose-phosphate pathway, and thus lead to dormancy termination, bud burst and rapid growth (17).…”
Section: Catalase In Grapevine Dormancy Results and Discussionsupporting
confidence: 75%
“…The activity of catalase was decreased by cool winter temperatures and dormancy-breaking chemicals such as cyanamide and thiourea. It is possible, as previously suggested for seeds (17,19,20), and found by us in grapevine buds (G. Nir, S Lavee, unpublished data), that the decrease in catalase activity causes an increase in the level of H202 in bud tissue. The increased level of H202 might cause the activation of the pentose-phosphate pathway, and thus lead to dormancy termination, bud burst and rapid growth (17).…”
Section: Catalase In Grapevine Dormancy Results and Discussionsupporting
confidence: 75%
“…The activation ofthe pentose-phosphate pathway is thought to be necessary for the breaking of dormancy in buds and seeds (19). Glucose-6-phosphate dehydrogenase, which catalyzes the rate limiting step in the pentose-phosphate pathway, is not only dependent on the availability of NADP+, but is inhibited by NADPH (6).…”
Section: Kiwifruitmentioning
confidence: 99%
“…They concluded that a block in phosphate metabolism appeared to be associated with the dormant state. Pradet et al (13) noted that the energy charge of germinating lettuce seeds was reduced under anaerobic conditions, and Simmonds and Simpson (17) found that dry storage of wild oat caryopses in an atmosphere of nitrogen resulted in a decreased rate of germination of the excised embryos in response to gibberellic acid while storage in oxygen resulted in an increased response of the embryos to gibberellic acid. Although Ching and Ching (6) recently observed a steep rise in the energy charge of embryos during stratification of ponderosa pine seeds, a causal relationship between the low temperature treatment and a high energy charge has not been established.…”
mentioning
confidence: 99%